Psychoanalytic thinking in occupational therapy : symbolic, relational, and transformative - Nicholls, Lindsey; Piergrossi, Julie Cunningham; Gibertoni, Carolina de Sena; Daniel, Margaret A. (Psychotherapist); Wiley eBooks (Chichester, West Sussex : Wiley-Blackwell, 2013)
This book explores the influence of psychoanalytic theories on occupational therapy practice and thinking. It incorporates a new conceptual model (the MOVI) to guide practice, which uses psychoanalysis as a theoretical foundation for understanding therapeutic relationships and the 'doing' that takes place in clinical practice.
The therapeutic use of self in occupational therapy -- An occupational therapy perspective on Freud, Klein, and Bion -- The function of doing in the intermediate space : Donald Winnicott and occupational therapy -- Beyond Bowlby : exploring the dynamics of attachment -- Re-awakening psychoanalytic thinking in occupational therapy : from Gail Fidler to here -- MOVI : a relational model in occupational therapy -- Let the children speak -- Working with difference -- Psychoanalytic thinking in research methods -- Understanding the use of emotional content in therapy using occupational therapists' narratives -- Training experiences to develop psychoanalytic thinking -- The relational space of supervision.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Occupational therapy -- Psychological aspects; Psychoanalysis; Occupational Therapy -- psychology; Psychoanalytic Theory; Psychotherapy; Occupational therapy -- Psychological aspects; Psychoanalysis; Electronic books